2018
DOI: 10.17681/hsp.348026
|View full text |Cite
|
Sign up to set email alerts
|

Ebelik ve Hemşirelik Öğrencilerinin Egzersiz Davranışı, Sigara Bağımlılığı ve Genel Sağlık Durumu

Abstract: Bağımlılık Testi'nden 0.26±0.99 puan aldığı görüldü. Yaş ile Egzersizde Davranışsal Düzenlemeler Ölçeği-2'nin güdülenmeme alt boyutu arasında negatif bir ilişki saptandı (r:-0.197, p:0.004). Katılımcıların vücut kütle indeksi değerleri ile Egzersizde Davranışsal Düzenlemeler Ölçeği-2'nin dışsal düzenleme alt boyutu arasında pozitif bir ilişki bulundu (r:0.215, p:0.002). Genel sağlık durumu ile egzersiz davranışı ve sigara bağımlılığı arasında istatistiksel olarak bir ilişki saptanmadı (p>0.05). Sonuç: Çalışmam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As the nursing students progress in their studies, differences in smoking behaviors for the different years of study occur. Studies have shown that senior nursing students are more likely to be smokers 24,[40][41][42] . The present study found the smoking level lower in first-year nursing students than in other classes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the nursing students progress in their studies, differences in smoking behaviors for the different years of study occur. Studies have shown that senior nursing students are more likely to be smokers 24,[40][41][42] . The present study found the smoking level lower in first-year nursing students than in other classes.…”
Section: Discussionmentioning
confidence: 99%
“…The highest score that can be obtained from the test is 10, and the lowest score is 0.24. The FTND scoring is evaluated as low (0-4 points), medium (5-6 points), high (7-8 points) and very high (9-10 points) 24 . The Turkish validity and reliability study of the FTND was performed by Uysal et al 20 (2004), who found it moderately reliable.…”
Section: Fagerström Test For Nicotine Dependencementioning
confidence: 99%